Analisis Usability Menggunakan Metode Heuristic Evaluation dan Web Usability Evaluation Tool pada Website ACC Career - Findra Kartika Sari Dewi; Yonathan Dri Handarkho; Felcia Veronica Prasetyo (Jurnal Buana Informatika, 2022)
Abstract. ACC Career website is a website from PT. Astra Credit Companies which aims for work applications. The website has been around for a long time but has never been updated. Recently, ACC has been revamping the website. Before the new website is launched, a usability evaluation is carried out using the heuristic evaluation and WEBUSE methods which aims to determine the website usability assessment for both the old and the new user interface. Usability is said to be good if users find it easy, happy and satisfied using the system. The heuristic evaluation method brings out problems in the system and recommendations for improvement from the evaluator. The Web Usability Evaluation Tool brings out usability levels based on the assessment of the questionnaire respondents. From the old website, the evaluator found 48 problems and the usability level obtained from the respondents' answers were Good for all categories. From the new website, the evaluators found 42 issues and the usability level was evenly divided between Good and Excellent.Keywords: Revamp, Website, Usability, Heuristic Evaluation, WEBUSE. Abstrak. Website ACC Career merupakan website dari PT. Astra Credit Companies (ACC) yang bertujuan untuk pengaplikasian pekerjaan. Website ini sudah ada sejak lama tetapi belum pernah ada pembaharuan. Baru-baru ini ACC sedang melakukan pengembangan ulang (revamp) website tersebut. Sebelum produk baru diluncurkan, diadakan evaluasi usability menggunakan metode Heuristic Evaluation dan WEBUSE yang bertujuan untuk mengetahui penilaian usability website baik untuk tampilan lama maupun tampilan yang sedang dikembangkan. Usability dikatakan baik jika pengguna mudah, senang, dan puas menggunakan sistem. Metode Heuristic Evaluation menghasilkan permasalahan yang ada pada sistem dan rekomendasi perbaikan dari evaluator. Metode Webuse menghasilkan tingkat usability berdasarkan penilaian responden kuisioner. Pada tampilan lama, evaluator menemukan 48 permasalahan dan level usability yang didapat dari jawaban responden adalah Good untuk seluruh kategori. Pada tampilan baru, evaluator menemukan 42 permasalahan dan level usability terbagi rata antara Good dan Excellent.Kata Kunci: Revamp, Website, Usability, Heuristic Evaluation, WEBUSE.